The Influence of Policy Implementation on the Effectiveness of the Waste Free Zone Program in Sukamiskin Village, Bandung City - Rachmawati, Emi; Arifin, Farid; Ramadhan, Fauzan Rasyadi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
One of the common issues faced by large cities is waste management, which can lead to a decline in environmental quality. This waste problem can escalate to health concerns and even socioeconomic issues. In response, the Waste-Free Area (Kawasan Bebas Sampah, KBS) policy was established. This policy defines an area where waste management is carried out independently by the community, based on five main principles: citizen involvement, independence, efficiency, environmental sustainability, and integration. At its core, policy implementation is a critical factor influencing the successful realization of the Waste-Free Area program.This study employs a quantitative descriptive method, using simple linear regression analysis to evaluate data collected from a sample in Sukamiskin Subdistrict. Primary data were obtained through questionnaires distributed by the researchers. The regression analysis is supported by validity and reliability tests, determination coefficient analysis, correlational analysis, and both partial and joint significance tests.The Waste-Free Area (KBS) program in Sukamiskin Subdistrict, Bandung City, aims to reduce household waste through 3R-based waste management (Reduce, Reuse, Recycle). While the program has potential, it has yet to achieve optimal outcomes due to low community participation, inadequate facility management, and limited coordination among stakeholders. The analysis reveals that policy implementation has a significant impact on the program’s effectiveness, contributing 47.2% to its success.